Analysis of Factors Influencing Choice of Institution for Professional Development: A Case Study of Post- Graduate Students’ Perceptions at the Catholic University of Eastern Africa in Kenya - Kalenya, Agnes K.; Amukowa, Wyclife O. (MCSER-CEMAS-Sapienza University of Rome, 2013)
Universities have play key roles in development human resources necessary for the growth of the institutions of the society, be it economic, political or social. To this regard university education has been regarded as the most important cycle in the education system. This explains the rapid expansion of university education in Kenya both in the public and private sector. Postgraduate education has become more marketable than ever before. This is because it provides candidates with specialized skills and competencies, paving way for promotion and widens career choices. Students seeking postgraduate studies apply to institutions of their choice. This paper is intrigued by one major issue: what makes a student to choose one university and not the other? It is in attempt to unravel the issue of choosing universities that this paper endeavours a finding with particular reference to The Catholic University of Eastern Africa.